Olfactory information processing viewed through mitral and tufted cell-specific channels - Hirata, Tatsumi (Frontiers in Neural Circuits, 2024)
Parallel processing is a fundamental strategy of sensory coding. Through this processing, unique and distinct features of sensations are computed and projected to the central targets. This review proposes that mitral and tufted cells, which are the second-order projection neurons in the olfactory bulb, contribute to parallel processing within the olfactory system. Based on anatomical and functional evidence, I discuss potential features that could be conveyed through the unique channel formed by these neurons.